Ensuring Data Privacy in the Age of Artificial Intelligence - Zahra, Yatama (Journal of Computer Science Application and Engineering (JOSAPEN), 2025)
This study explores the intersection of data privacy and artificial intelligence (AI) within the context of Indonesia’s evolving digital landscape. As AI technologies become increasingly embedded in key sectors such as healthcare, finance, education, and public services, the need for robust data protection mechanisms grows more urgent. The 2022 enactment of Indonesia’s Personal Data Protection (PDP) Law marks a significant step toward safeguarding individual privacy rights and regulating the use of personal data in AI systems. However, challenges remain in ensuring compliance with legal principles such as transparency, purpose limitation, and user consent, especially as many AI models operate as opaque "black boxes." Through a comparative analysis of global data privacy regulations—including the GDPR, CCPA, and PIPL—this study highlights international best practices and their relevance to AI governance. A conceptual framework is presented to illustrate the foundational principles necessary for aligning AI development with data privacy standards. The study concludes by emphasizing the importance of a harmonized, ethics-driven regulatory approach that supports responsible AI innovation while protecting individual rights. Stronger collaboration among government, industry, and civil society is essential to achieving a secure, trustworthy, and inclusive digital future for Indonesia.